2021
DOI: 10.1111/tan.14334
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐G expression correlates with histological grade but not with prognosis in colorectal carcinoma

Abstract: Trophoblast‐specific expression of HLA‐G induces immune tolerance for the developing fetus. Pathological HLA‐G expression later in life might contribute to immune escape of various cancers. We studied the still controversial role of HLA‐G in colorectal carcinoma (CRC) using the MEM‐G/1 antibody and a tissue microarray series of CRC tumors (n = 317). HLA‐G expression appeared in 20% of the tumors and showed high intratumoral heterogeneity. HLA‐G positivity was associated with better differentiation (p = 0.002) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Favoring HLA-G’s harmful impact on CRC patient prognosis, three studies have shown a significantly reduced OS (HR 3.14, p = 0.021; HR 0.311, p = 0.008 and HR 1.428, p = 0.044 respectively) in the HLA-G positive subgroup (Ye et al 2007 ; Guo et al 2015 ; Zhang et al 2017 ). On the other hand, three different studies did not identify any impact of HLA-G expression on patient prognosis (Fukushima et al 1998 ; Kaprio et al 2021 ; Zeestraten et al 2014 ). A peculiar finding was that of Reimers et al who demonstrated that patients with rectal cancer strongly expressing HLA-G showed prolonged DFS (HR 0.75; p = 0.042) compared to the 350 cases with a weak HLA-G expression (Reimers et al 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Favoring HLA-G’s harmful impact on CRC patient prognosis, three studies have shown a significantly reduced OS (HR 3.14, p = 0.021; HR 0.311, p = 0.008 and HR 1.428, p = 0.044 respectively) in the HLA-G positive subgroup (Ye et al 2007 ; Guo et al 2015 ; Zhang et al 2017 ). On the other hand, three different studies did not identify any impact of HLA-G expression on patient prognosis (Fukushima et al 1998 ; Kaprio et al 2021 ; Zeestraten et al 2014 ). A peculiar finding was that of Reimers et al who demonstrated that patients with rectal cancer strongly expressing HLA-G showed prolonged DFS (HR 0.75; p = 0.042) compared to the 350 cases with a weak HLA-G expression (Reimers et al 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“… 10% Zhang et al ( 2017 ) 457 I–IV 49% (NAT n.a.) Whole slide 4H84 > 5% 70.7% No impact OS > 55% 59.7% Negative impact Kaprio et al ( 2021 ) 307 I–IV 54% (NAT n.a.) TMA MAI-19219 n.a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a different study, HLA-G expression in renal cancer tissue was demonstrated to be significantly higher than that in adjacent normal tissue, and the frequency of upregulated expression of HLA-G was significantly higher than that of other HLA antigens (72). HLA-G expression in patients with esophageal cancer, HCC and colorectal cancer has also been demonstrated to be significantly higher than that in healthy volunteers, and this was correlated with TNM stage, tumor histological grade, invasion degree, lymph node status and the immune response (73)(74)(75). The postoperative survival time of patients with HCC and with HLA-G + expression was significantly shorter than that of patients with HLA-Gexpression.…”
Section: Hla Polymorphism and Cancermentioning
confidence: 95%
“…This induces a transformation in macrophages towards the M2 phenotype (SPP1+ macrophages). SPP1+ macrophages attract regulatory T (Treg) and CD8+ T cells into CRC tissues, leading to anti-tumor immune resistance and depletion of CD8+ T cells (115,116).…”
Section: Human Leukocyte Antigen G and Ementioning
confidence: 99%